Cardiac Rehabilitation - Kraus, William; Keteyian, Steven; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2007)
Cardiac rehabilitation can be extremely complex art. In Cardiac Rehabilitation, expert authors provide state-of-the-art information that serves as a manual to the multidisciplinary nature of cardiac rehabilitation in the current era, the current state of cardiac rehabilitation, and the issues facing current CR programs. Covering the major components of a CR program, including medical therapy, exercise, nutrition, and behavioral therapy, from referral to testing to individualizing the program for the participants, the volume is a thorough, vital guide to this important field. Comprehensive and substantial, Cardiac Rehabilitiation will aid cardiologists and internal specialists greatly in saving the lives of heart patients across the globe.
Principles for Prescribing Exercise in Cardiovascular Disease -- Nutrition in Cardiac Rehabilitation -- References -- Assessment and Management of Depression in Cardiac Rehabilitation Patients -- Managing Stress to Manage Heart Disease -- Use of Readiness for Change in Cardiac Rehabilitation Programs -- Smoking Cessation: The Prescription that Every Smoker Should be Given -- Utility of Graded Exercise Testing in the Cardiac Rehabilitation Setting -- Graded Exercise Testing -- The Use of Cardiopulmonary Exercise Testing in Cardiac Rehabilitation: A Primer and Case Analysis -- Role of the 6-Minute Walk Test in Cardiac Rehabilitation -- Cardiac Rehabilitation: Statins and the Rationale for Implementation of Lipid-Lowering Therapy -- Treating to Goal: Diabetes and Hypertension -- Exercise in Patients with Cardiovascular Disease -- Exercise as a Therapeutic Intervention for Hypertension -- Diabetes Mellitus and Cardiac Rehabilitation in Clinical Practice -- Pulmonary Issues Related to Cardiac Rehabilitation -- Exercise Rehabilitation for Patients with Peripheral Arterial Disease -- Dealing with Arthritis as a Comorbidity in Cardiac Rehabilitation Programs -- Cardiac Rehabilitation for Elderly Cardiac Patients -- Expanding Your Model: Optimizing Referrals and Introducing Disease Management -- The Role of the Physician-Medical Director in Cardiac Rehabilitation -- Assessment and Treatment of Risk in the Clinic Setting -- Cardiac Rehabilitation Staffing -- Reimbursement Issues.
Keywords: Cardiology; Rehabilitation medicine; Internal medicine; Cardiology; Rehabilitation Medicine; Internal Medicine